The Occurrence of Nitrate Reductase in Apple Leaves - Klepper, Lowell (1969)
Nitrate reductase utilizing NADH or reduced flavin mononucleotide (FMNH(2)) as electron donor was extracted from the leaves, stems and petioles, and roots of apple seedlings. Successful extraction was made possible by the use of insoluble polyvinylpyrrolidone (Polyclar AT) which forms insoluble complexes with polyphenols and tannins. The level of nitrate reductase per gram fresh weight was highest in the leaf tissue although the nitrate content of the roots was much higher than that of the leaves. Nitrite reductase activity was detected only in leaf extracts and was 4 times higher than nitrate reductase activity. Nitrate was found in all parts of young apple trees and trace amounts were also detected in mature leaves from mature trees. Nitrate reductase was induced in young leaves of apple seedlings and in mature leaves from 3 fruit-bearing varieties. An inhibitor of polyphenoloxidase, 2-mercaptobenzothiazole was used in both the inducing medium and the extracting medium in concentrations from 10(−3) to 10(−5)m with no effect upon nitrate reductase activity.